Stockholm preterm interaction-based intervention (SPIBI) - study protocol for an RCT of a 12-month parallel-group post-discharge program for extremely preterm infants and their parents - Erika Baraldi; Mara Westling Allodi; Kristina Löwing; Ann-Charlotte Smedler; Björn Westrup; Ulrika Ådén (BMC, 2020)
Abstract Background Improved neonatal care has resulted in increased survival rates among infants born after only 22 gestational weeks, but extremely preterm children still have an increased risk of neurodevelopmental delays, learning disabilities and reduced cognitive capacity, particularly executive function deficits. Parent-child interaction and parental mental health are associated with infant development, regardless of preterm birth. There is a need for further early interventions directed towards extremely preterm (EPT) children as well as their parents. The purpose of this paper is to describe the Stockholm Preterm Interaction-Based Intervention (SPIBI), the arrangements of the SPIBI trial and the chosen outcome measurements. Methods The SPIBI is a randomized clinical trial that includes EPT infants and their parents upon discharge from four neonatal units in Stockholm, Sweden. Inclusion criteria are EPT infants soon to be discharged from a neonatal intensive care unit (NICU), with parents speaking Swedish or English. Both groups receive three initial visits at the neonatal unit before discharge during the recruitment process, with a strengths-based and development-supportive approach. The intervention group receives ten home visits and two telephone calls during the first year from a trained interventionist from a multi-professional team. The SPIBI intervention is a strengths-based early intervention programme focusing on parental sensitivity to infant cues, enhancing positive parent-child interaction, improving self-regulating skills and supporting the infant's next small developmental step through a scaffolding process and parent-infant co-regulation. The control group receives standard follow-up and care plus extended assessment. The outcomes of interest are parent-child interaction, child development, parental mental health and preschool teacher evaluation of child participation, with assessments at 3, 12, 24 and 36 months corrected age (CA). The primary outcome is emotional availability at 12 months CA. Discussion If the SPIBI shows positive results, it could be considered for clinical implementation for child-support, ethical and health-economic purposes. Regardless of the outcome, the trial will provide valuable information about extremely preterm children and their parents during infancy and toddlerhood after regional hospital care in Sweden. Trial registration The study was registered in ClinicalTrials.gov in October 2018 (NCT03714633).